Package C Nonformal School Students' Reading Comprehension Strategy of PKBM Iftitah Padang Panjang - Oklid, Tsabithah Salsabilla; Addinna, Ainul (Journal of English Language Teaching, 2024)
The aim of the current study was to explore the reading comprehension strategies used by nonformal school students on academic English texts. A descriptive quantitative method was employed for this research. The population consisted of all 81 students enrolled at PKBM Iftitah Padang Panjang's tenth, eleventh, and twelve grades. The sample was chosen using the total sampling. A reading comprehension test and the SORS questionnaire were used to collect the data. There are fifteen questions in the reading test, ten of which are multiple-choice and five of which are essay-based. The data were analyzed through reflecting to the Syllabus of the 2013 Curricula’s Basic Competencies (KD). The study's findings indicated that the students' comprehension was rated as poor, with an overall mean score of 53.88. Besides, the questionnaire revealed that most students relied on Problem-Solving Strategies. It was proved by the mean score 3.54, while the dimension that was most frequently used—"I try to get back on track when I lose concentration"—received the highest mean score of 4.18. The findings show that the nonformal students prioritize actively addressing moments of distraction or loss of focus during their reading, underscoring their proactive approach to overcoming comprehension challenges.